2017
DOI: 10.1287/mksc.2017.1029
|View full text |Cite
|
Sign up to set email alerts
|

First-Mover Advantage Through Distribution: A Decomposition Approach

Abstract: Whereas the extant literature on entry-order e¤ects establishes that …rst entrants often earn higher market shares ("market-share advantage"), the literature on distribution suggests increased distribution has a positive e¤ect on sales. Can distribution help us better understand entry-order e¤ects on market shares? This paper examines how the …rst entrant in a geographical market achieves a market-share advantage through distribution. For this purpose, I propose a simple method of decomposing sales into physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 59 publications
(60 reference statements)
1
2
0
Order By: Relevance
“…We found that executives in all seven countries expected a performance outcome advantage for sustainability first-movers. This result provides additional empirical evidence that supports prior first-mover research findings [8][9][10]23,[41][42][43][44]. Executives from the United States and the United Kingdom perceived performance benefits to sustainability first-movers to be significantly greater than the level perceived by executives from the other countries, particularly Germany and China.…”
Section: Theoretical Implicationssupporting
confidence: 78%
“…We found that executives in all seven countries expected a performance outcome advantage for sustainability first-movers. This result provides additional empirical evidence that supports prior first-mover research findings [8][9][10]23,[41][42][43][44]. Executives from the United States and the United Kingdom perceived performance benefits to sustainability first-movers to be significantly greater than the level perceived by executives from the other countries, particularly Germany and China.…”
Section: Theoretical Implicationssupporting
confidence: 78%
“…Likewise, the ability to adapt to market changes contributes to exploiting the market first and improving business performance (Huang & Wang, 2011). Companies that explore the market first generate competitive advantages and have the potential to lead the market and improve performance (Davcik & Sharma, 2016;Nishida, 2017). Therefore, companies need to develop summer days both individually and in teams so that performance continues to improve (Ferdinand & Wahyuningsih, 2018).…”
Section: Preemptive Market Exploitability and Marketing Performancementioning
confidence: 99%
“…First, the greater the distance from JD's headquarters, the higher the operating costs (Jia 2008;Kalnins and Lafontaine 2013;Nishida 2017;Zhu and Singh 2009) and the less likely the city is a candidate for the ODS launch. The idea behind this correlation is that the cost of sending a company employee to monitor the outlet in a given market may increase as the distance between the market and headquarters increases (Nishida 2017).…”
Section: Endogeneity and Self-selectionmentioning
confidence: 99%
“…First, the greater the distance from JD's headquarters, the higher the operating costs (Jia 2008;Kalnins and Lafontaine 2013;Nishida 2017;Zhu and Singh 2009) and the less likely the city is a candidate for the ODS launch. The idea behind this correlation is that the cost of sending a company employee to monitor the outlet in a given market may increase as the distance between the market and headquarters increases (Nishida 2017). Table 3 reports the first-stage results from the probit Second, distance from JD's headquarters is a naturally occurring geographical value in each city and has been used as an instrumental variable in the U.S. market.…”
Section: Endogeneity and Self-selectionmentioning
confidence: 99%